The Effect of Quora Application on Students’ Higher-Order Thinking Skills at SMAN 4 Kendari - Aprianti, Sitti Fatimah; Hanna, Hanna; Nurnia, Nurnia (Journal of Teaching of English, 2021)
This study aims at finding out whether there is a significant effect of using Quora application on students’ higher-order thinking skills at eleventh-grade students of SMAN 4 Kendari. This study was a quantitative pre-experimental method with one-group pretest-posttest design. The sample was students at XI IPA 1 class consisting of 36 students. In collecting the data, the researcher used reading test which consisted of 19 items in essay forms. The finding of this study showed that there is a significant effect of using Quora application on students' higher-order thinking skills. It was proven by the increase in students’ mean scores from pretest to posttest. The mean score for the pretest was 58.69 and standard deviation of 9.558 and the post-test was 75.36 and a standard deviation of 8.232. It can be seen that students' higher-order thinking skills were improved after being taught by using Quora application. Furthermore, this study proved that H0 was rejected and H1 was accepted with the value of Sig (2 tailed) 0.000 which was lower than the alpha value α (0.05) or sig (2 tailed) 0.000 < 0.05. Based on the findings, it can be concluded that there was a significant effect of using Quora application on students’ higher-order thinking skills at SMAN 4 Kendari.